2016
DOI: 10.18632/oncotarget.11492
|View full text |Cite
|
Sign up to set email alerts
|

KIF-2C expression is correlated with poor prognosis of operable esophageal squamous cell carcinoma male patients

Abstract: To determine the prognostic significance of Kinesin family member 2C (KIF-2C) expression in patients with operable esophageal squamous cell carcinoma (ESCC), we conducted an immunohistochemical analysis of KIF-2C expression in 415 surgically resected primary tumor tissues and 40 adjacent non-cancerous tissues from patients with operable ESCC. The median duration of postoperative follow-up was 76.0 months. Higher KIF-2C expression was associated with significantly increased risks of higher pathologic tumor (pT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…KIFs participate in various physiological activities related to cellular motility. Substantial evidence verifies that KIFs participate in the malignant biological behavior of cancers . KIF2A and KIF2C are overexpressed in immortalized human bronchial epithelial cells, and subsequently promote EMT in cancer cells .…”
Section: Discussionmentioning
confidence: 98%
“…KIFs participate in various physiological activities related to cellular motility. Substantial evidence verifies that KIFs participate in the malignant biological behavior of cancers . KIF2A and KIF2C are overexpressed in immortalized human bronchial epithelial cells, and subsequently promote EMT in cancer cells .…”
Section: Discussionmentioning
confidence: 98%
“…KIF2C is up‐regulated in glioma samples compared with normal brain tissues, and it is associated with histopathological grades . In esophageal squamous cell carcinoma, prognosis was worse for male patients with higher KIF2C expression compared with other patients at the same TNM stage …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that many KIFs are involved in the carcinogenesis of multiple human cancers, including lung cancer [17][18][19][20][21][22]. For example, KIFC1 is upregulated in human breast cancer [19], whereas KIF2C is upregulated in esophageal squamous cell carcinoma and is associated with poor prognosis [22].…”
Section: Discussionmentioning
confidence: 99%
“…For example, KIFC1 is upregulated in human breast cancer [19], whereas KIF2C is upregulated in esophageal squamous cell carcinoma and is associated with poor prognosis [22]. KIF14 expression is significantly increased in cervical tumor tissues, and its expression is positively associated with a high tumor stage, lymph node metastasis, and chemoresistance [23].…”
Section: Discussionmentioning
confidence: 99%